Finite element analysis of slab bridge with beam element using ANSYS - Ho, Kit Sheng (2019)
In this research, a beam bridge model has been analysed by using ANSYS. This research is to investigate the adequacy of reinforcement and also checking the structural behaviour of the structure according to Eurocode 2. The structure is analyse using finite element analysis using ANSYS to check the adequacy of the reinforcement. From the result of simulation, we can know the behaviour of the structure under the input parameter that applied. Beside these, by carrying out the probabilistic analysis, we collected the result of cumulative distribution function, the histogram plot, sensitivity plot and simple history plot for all parameter. These plots shows the information such as mean value, standard deviation, minimum value, maximum value, skewness and kurtosis of the parameters. The values for the output parameter were generated with Monte Carlo simulation randomly. The output parameter is generated based the input parameter generated through probabilistic analysis with ANSYS probabilistic design system. The mean value, standard deviation, sample values minimum value, maximum value, skewness and kurtosis of the output parameter is presented through sample history plot. 5000 loops of probabilistic analysis simulation is done, to ensure that the result of analysis is precise and uniform. The length of the model is 20m. At last, some suggestions is given to improve the ANSYS software to make sure the best user experience.